Why Should Emerging Economies Give Up National Currencies? A Case for Institutions Substitution - Enrique Mendoza (Inter-American Development Bank, Research Department, 2002)
Financial contagion and Sudden Stops of capital inflows experienced in emerging-markets crises may originate in an explosive mix of lack of policy credibility and world capital market imperfections that afflict emerging economies with national currencies. Hence, this paper argues that abandoning national currencies to adopt a hard currency can significantly reduce the emerging countries` vulnerability to these crises. The credibility of their financial policies would be greatly enhanced by the implicit subordination to the policymaking institutions of the hard currency issuer. Their access to international capital markets would improve as the same expertise and information that global investors already gather to evaluate the monetary policy of the hard currency issuer would apply to emerging economies. Yet, adopting a hard currency does not eliminate business cycles, rule out all forms of financial crises, or solve severe fiscal problems that plague emerging economies, and it entails giving up seigniorage and potential benefits of conducting independent monetary policy. However, these disadvantages seem dwarfed by the urgent need to enable emerging countries to access global capital markets without exposing them to the risk of recurrent Sudden Stops.
Keywords: 330; Währungssubstitution; Glaubwürdigkeit; Internationaler Finanzmarkt; Kapitalmobilität; Schwellenländer; Welt; Finanzkrise